Is There a Way in the Labyrinth of Treaty Norms Leading to the Applicable Rule?: Investor-State Investment Settlement under the China-Korea FTA, China-Japan-Korea BIT and China-Korea BIT - Qingjiang, Kong (Columbia Journal of Asian Law, 2016)
With the signature of the Free Trade Agreement between the People’s Republic of China and the Republic of Korea (CK FTA) in 2015 and subsequent ratification, there will be three sets of rules with respect to investment flow between China and Korea, i.e. the Agreement among the Government of the People’s Republic of China, the Government of Japan and the Government of the Republic of Korea on the Promotion and Protection of Investment. A quick look at these rules will show that there are overlapping and even conflicts among them. While the agreements were designed to facilitate the investment flow between the countries concerned, the rules will pose intimidating barriers to the investors. And even for professional lawyers, this will be a labyrinth of treaty norms. A question arises in this regard: shall there be an integrated approach so that there will be a coherent cannon of rules, which encompass a recognition of the rules in CK FTA, CJK BIT and CK BIT as mutually complimentary to each other, and lex posterior derogat priori. The article is to be structured as follows: Part A is an introduction that highlights the issues; Part B is an examination of the major investments rules in the three sets of IIAs mentioned-above; Part C focuses on a discussion of how to determine the applicable rules among various treaties under the Vienna Convention and Part D concludes the article with a few remarks in the context of the IIAs.